Dissociation of Ionic Surfactants at the Air/Water Interface: Complete or Partial? - Phan, Chi (American Chemical Society, 2016)
© 2016 American Chemical Society.This article reconsiders the current theory on the interfacial adsorption of ionic surfactants. In particular, the dissociation degree of the adsorbed surfactants was critically re-examined. A new modeling framework was developed to include partial dissociation into the current theory. The model was verified, with physically consistent parameters, for two cationic surfactants. Partial dissociation can resolve some of the abnormalities in the literature. Finally, the future direction for surface studies, which will need to include this factor, is presented.